Women's Access to Sharia Financing Products and Its Impact on Family Welfare - Alting, Rosita (Manunggal Halim Jaya, 2025)
This study aims to analyze the impact of women's access to Islamic financing products on family welfare. The study used a qualitative approach with a case study method conducted on female customers of Islamic financial institutions in Ternate City. Data were collected through in-depth interviews, observation, and documentation, then analyzed using thematic analysis. The results show that access to Islamic financing has a positive impact on five main dimensions of family welfare: improving household finances, continuing children's education, improving health quality, household harmony, and women's empowerment. Islamic financing schemes such as murābaḥah, qardhul ḥasan, and microfinance help women increase business capacity, allocate funds for education and health, and create family stability. This study confirms that Islamic financing is not only an economic instrument, but also a social and spiritual instrument that supports the achievement of maqāṣid al-syarī'ah and holistic family welfare.